Growth Differentiation Factor-15 as a Biomarker for Sarcopenia in Patients With Chronic Obstructive Pulmonary Disease - Deng, Mingming; Bian, Yiding; Zhang, Qin; Zhou, Xiaoming; Hou, Gang (Frontiers in Nutrition, 2022)
Purpose: Sarcopenia is an important factor contributing to comorbidity in patients with chronic obstructive pulmonary disease (COPD) and is an independent risk factor for increased mortality. The diagnostic process for sarcopenia requires specific equipment and specialized training and is difficult procedurally. A previous study has found that GDF15 levels are associated with skeletal muscle mass and function in patients with COPD. However, whether circulating GDF15 levels can be used for the prediction of sarcopenia in patients with COPD is unknown. Methods: This study included 235 patients with stable COPD, who were divided into a development set(n=117) and a validation set(n=118) and we followed the definition of sarcopenia as defined by the guidelines from the Asian Working Group for Sarcopenia. Serum concentrations of GDF15 were measured using an enzyme-linked immunosorbent assay and construction of a nomogram and decision curve analysis were performed using R package “rms”. Results: In this study, serum GDF15 levels were negatively associated with skeletal muscle mass (r = −0.204, p = 0.031), handgrip strength (r = −0.274, p = 0.004), quadriceps strength (r = −0.269, p = 0.029), and the thickness (r = −0.338, p < 0.001) and area (r = −0.335, p < 0.001) of the rectus femoris muscle in patients with COPD. Furthermore, the serum levels of GDF15 in patients with sarcopenia were significantly higher than controls, Importantly, serum levels of GDF15 could effectively predict sarcopenia in patients with COPD based on the development set (AUC = 0.827) and validation set (AUC = 0.801), and the cutoff point was 357.5 pg/ml. Finally, a nomogram model based on serum GDF15 level and clinical features showed good predictive ability (AUC>0.89) in the development and validation sets. Conclusion: Serum GDF15 level could be used to accurately and easily evaluate sarcopenia in patients with COPD.